2017
DOI: 10.1126/sciadv.1602102
|View full text |Cite
|
Sign up to set email alerts
|

Structural transitions and guest/host complexing of liquid crystal helical nanofilaments induced by nanoconfinement

Abstract: A perfectly aligned liquid crystal phase can be achieved by an interaction with helical nanofilament under nanoconfinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…These structural parameters are comparable to those previously reported for helical nanofilaments formed by liquid crystals. 75 Using AFM, we were able to assess the vertical thickness (height) of a single HNF@Au@L fiber, to be ∼35 nm ( Figure 2 f–h, Figure S6 ). The small discrepancy between the values of the lateral thickness and height can be explained by the soft character of the composite, which leads to fibers flattening on the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These structural parameters are comparable to those previously reported for helical nanofilaments formed by liquid crystals. 75 Using AFM, we were able to assess the vertical thickness (height) of a single HNF@Au@L fiber, to be ∼35 nm ( Figure 2 f–h, Figure S6 ). The small discrepancy between the values of the lateral thickness and height can be explained by the soft character of the composite, which leads to fibers flattening on the substrate.…”
Section: Resultsmentioning
confidence: 99%
“… 56 The final state is a conglomerate structure made of domains with both left and right handedness. Given the possibility of characterizing homochiral domains using far field methods, as well as the versatility and plasticity of soft, 57 60 thermotropic LC thin films, these materials can be of high technological relevance. 61 65 Recently, some of us demonstrated the incorporation of metal nanoparticles into HNF materials.…”
mentioning
confidence: 99%
“…HNFs strongly depended on the mixture parameters and pore dimensions of NP-AAO. [374][375][376][377] It should be noted that HNFs of Reproduced with permission. [360] Copyright 2009, AAAS.…”
Section: Bent-core Liquid Crystalsmentioning
confidence: 99%
“…In particular, Guo et al ( 34 ) have recently shown that the process based on plasmonic mask photoalignment is a way to produce the desired topological LC defect patterns on demand, although it requires expensive photolithographic tools and does not show reconfigurable characteristics. In contrast to electric or magnetic field controlling the orientation of LC materials in a whole volume, topographical confinement effectively produces more complex and precisely assembled LC structures on a scale of a few micrometers because the confinement can be finely controlled even on the nanometer scale, which provides a rich variety of boundary conditions ( 35 ). The strategy using confinement enables the minimization of the total free energy of the LC structure (bulk elasticity and surface anchoring) in the equilibrium state.…”
Section: Introductionmentioning
confidence: 99%